Poverty and exclusion in urban China - Yan Hao (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
This paper discusses how widespread poverty and exclusion are in urban China during the period of transition from central planning to a market economy. Two poverty lines have been employed to measure poverty rates in urban areas: a diagnostic poverty line calculated by the Asian Development Bank (ADB) experts and a benefit poverty line used in the Minimum Living Allowance Program of the Chinese government. Both sets of estimates show marked variations by province. According to the former standard, the poverty headcount of China in 1998 was estimated as 14.8 million, with a poverty rate of 4.7 percent. According to the later standard, the poverty headcount for 2007 is estimated as 22.7 million, amounting to a poverty rate of 3.9 percent. Poor people are generally not living in absolute poverty, as their basic needs in food, clothing and shelter can largely be met. However, they have low incomes and restricted consumption potential. Economic constraints also entail adverse consequences like poor health, poor education and limited social contacts. Two groups of people are here considered as the new poor: unemployed or laid-off workers and labor migrants. This means that China now has two new forms of urban poverty which are caused by different factors and are combined with different forms of deprivation. Therefore, policy programs designed to eradicate poverty in urban areas have to be tailored carefully to the poor people's special needs. Job creation and a comprehensive social protection system are here proposed as two effective instruments in the fight against urban poverty.
Keywords: 300